Nano-film silicon-based hydrogel drug-loaded contact lens and preparation method thereof

By forming a nanofilm on the surface of the contact lens and combining nanocarriers of mesoporous silica and chitosan, the problem of low efficacy of existing silicon hydrogel contact lenses is solved, achieving high oxygen permeability and continuous eye treatment effect.

CN119472078APending Publication Date: 2025-02-18深圳市瞳学科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590071.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The efficacy of existing drug-loaded silicone hydrogel contact lenses cannot meet expectations, and due to low oxygen permeability, it may lead to corneal hypoxia and risk of inflammation.

Method used

Using nano-film silicon-based hydrogel contact lenses, nano-film containing drug molecules is formed on the surface of the contact lens body, and nano-carriers prepared by combining mesoporous silica and chitosan to improve the drug load and sustained release effect. And the oxygen permeability is improved by siloxane monomer and hydrophilic monomer.

Benefits of technology

It significantly improves drug retention and sustained release time, reduces adverse reactions, achieves eye treatment with high oxygen permeability, and extends the retention time of drug in the eyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119472078A_ABST
    Figure CN119472078A_ABST
Patent Text Reader

Abstract

The invention provides a nano-film silicon-based hydrogel drug-loaded contact lens and a preparation method thereof.The nano-film silicon-based hydrogel drug-loaded contact lens comprises a contact lens body and a film which is arranged on the surface of the contact lens body and contains drug molecules, the thickness of the film is 0.5-10 microns, the nano-structure monomer aperture of the film is 50-1000 nm, and the contact lens body has the oxygen permeation coefficient of 100-150; the contact lens is prepared from 0-90% of a contact lens base material, 0.1-5% of a nano-carrier, 0-20% of a cross-linking agent and 0-8% of an initiator. Wherein the nano-carrier is prepared from mesoporous silica and chitosan, the mesoporous silica has nano-pores with different pore diameters, and the nano-pores are loaded with hydrophilic or hydrophobic drug molecules. Drug molecules with different molecular weights are loaded by nano-carriers with different apertures, so that the silicone hydrogel contact lens has the functions of loading a large amount of drugs and slowly releasing the drugs, the retention time of the drugs in eyes is prolonged, the silicone hydrogel contact lens has high oxygen permeability, the drug retention rate can be obviously improved, adverse reactions are reduced, and continuous eye treatment can be carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of contact lenses, and in particular to a nano-thin film silicon-based hydrogel drug-loaded contact lens and a preparation method thereof. Background Art

[0002] Nowadays, many eye diseases still rely on traditional drug preparations such as ophthalmic preparations for treatment. However, due to the particularity of the physiological structure of the eye (such as the renewal of the tear film, corneal permeability and other factors), it is difficult for ophthalmic drugs to reach an effective concentration, the drug retention rate is low, and some traditional ophthalmic preparations may irritate the eyes. Therefore, it is particularly important to develop new ophthalmic drugs.

[0003] Drug-loaded contact lenses solve the above problems well and can prolong the retention time of drugs in the eye. However, the oxygen permeability (Dk) of hydrogel contact lenses is an average of 20 to 30, which causes the wearer's cornea to be in a state of long-term hypoxia, which not only leads to corneal vascular hyperplasia, but also may increase bacterial adhesion and increase the risk of corneal inflammation. Silicone-based hydrogel is a hydrophilic organic polymer material. It is a new type of material that combines the high permeability of silicone rubber and the softness of hydrogel. It can transport oxygen through two channels, the silicone phase and the hydrogel phase, to achieve higher oxygen permeability. It is an ideal material for the development of highly oxygen-permeable soft corneal contact lenses. However, the current drug loading of drug-loaded silicone hydrogel contact lenses is average, resulting in its efficacy failing to meet expectations. Summary of the invention

[0004] In view of the above problems, the present application is proposed to provide a nano-thin film silicon-based hydrogel drug-loaded contact lens and a preparation method thereof that overcomes the above problems or at least partially solves the above problems, comprising:

[0005] A nano-film silicon-based hydrogel drug-carrying contact lens, comprising a contact lens body and a film containing drug molecules disposed on the surface of the contact lens body, wherein the film has a thickness of 0.5 to 10 microns, a nanostructure monomer pore size of 50 nm to 1000 nm, and the contact lens body has an oxygen permeability coefficient of 100 to 150;

[0006] The contact lens is made of 0-90% of a contact lens substrate, 0.1-5% of a nanocarrier, 0-20% of a crosslinker and 0-8% of an initiator; wherein the nanocarrier is prepared from mesoporous silica and chitosan, the mesoporous silica has nanopores with different pore sizes, and the nanopores are loaded with hydrophilic or hydrophobic drug molecules.

[0007] Further, the drug molecule solution includes ophthalmic drug molecules and a drug solvent;

[0008] The ophthalmic drug molecules include one or more of ketotifen, levofloxacin, lomefloxacin, moxifloxacin, gentamicin, tetracycline hydrochloride or tobramycin, vitamin B12, vitamin B6, vitamin E, polymyxin sulfate, dexamethasone, hydroxypropyl methylcellulose and hyaluronic acid;

[0009] The drug solvent includes one or more of water, PBS buffer, polyethylene glycol, acetic acid solution, ethanol and physiological sodium chloride solution.

[0010] Furthermore, the contact lens substrate comprises 35-65% of siloxane monomers, 35-65% of hydrophilic monomers and 0.01-0.5% of color dyes.

[0011] Furthermore, the siloxane monomer includes one or more of bis-3-methacryloxypropylated tetramethyldisiloxane, methacryloxypropyl tris(trimethylsiloxy)silane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methyl.

[0012] Furthermore, the hydrophilic monomer includes one or more of hydroxyethyl methacrylate, N-vinyl pyrrolidone, methacrylic acid, methyl methacrylate and polyethylene glycol methacrylate.

[0013] Furthermore, the color fuel includes one or more of benzidine yellow, carbon black, phthalocyanine blue, phthalocyanine green, iron oxide violet, iron oxide black, iron oxide red, iron oxide yellow and titanium dioxide.

[0014] Furthermore, the crosslinking agent includes one or more of PVA, PVP, PEO, PAA, hyaluronic acid, polysiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, mercaptopropionic acid, citric acid and polyether polyurethane acrylate macromolecular crosslinking agents.

[0015] Further, the initiator includes one of 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile) and phenylbisphosphine oxide.

[0016] The present invention also provides a method for preparing a nano-thin film silicon-based hydrogel drug-loaded contact lens, comprising the steps of:

[0017] uniformly mixing the drug molecules, the nanocarrier, the contact lens substrate, the crosslinking agent and the initiator to obtain a mixed solution;

[0018] The mixed solution is sprayed on the surface of the contact lens body to form a thin film to obtain the target contact lens.

[0019] Furthermore, it also includes:

[0020] Mixing a silica template, polyether and pure water, adding a sodium hydroxide solution, and heating the mixture at 40-60° C. for 1-2 hours; wherein the silica template comprises one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium toluenesulfonate;

[0021] The mixed solution is mixed with tetraethoxysilane and reacted at 50-70° C.;

[0022] Purifying the reaction product and calcining it at 500-600° C. for 5-7 hours to obtain mesoporous silica;

[0023] The chitosan solution, the mesoporous silica and sodium tripolyphosphate are mixed and stirred for 0.5 h, and then centrifuged and dried to obtain the nanocarrier; wherein the solvent of the chitosan solution is 2% acetic acid solution.

[0024] This application has the following advantages:

[0025] In the embodiments of the present application, with respect to the technical problem in the prior art that "the current drug-loaded silicone hydrogel contact lenses have a general drug loading amount, resulting in their efficacy failing to meet expectations", the present application provides a solution for loading drug molecules with nanocarriers having nanopores of different pore sizes, specifically: comprising a contact lens body and a film containing drug molecules disposed on the surface of the contact lens body, the film having a thickness of 0.5 to 10 microns, a nanostructure monomer pore size of 50nm-1000nm, and the contact lens body having an oxygen permeability coefficient of 100-150; the contact lens is made of a contact lens substrate accounting for 0-90%, a nanocarrier of 0.1-5%, a cross-linker of 0-20% and an initiator of 0-8%; wherein the nanocarrier is prepared from mesoporous silica and chitosan, the mesoporous silica having nanopores of different pore sizes, and the nanopores are loaded with hydrophilic or hydrophobic drug molecules. By using nanocarriers with different pore sizes to load drug molecules of different molecular weights, silicone hydrogel contact lenses have the functions of large-scale drug loading and sustained release, which prolongs the retention time of drugs in the eye. With high oxygen permeability, they can significantly improve drug retention rate, reduce adverse reactions, and allow continuous eye treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the description of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 This is a flow chart of the steps of a method for preparing a nano-thin film silicon-based hydrogel drug-loaded contact lens provided in one embodiment of the present application;

[0028] Figure 2 is a flow chart of the preparation steps of a nanocarrier provided in one embodiment of the present application;

[0029] Figure 3 It is a schematic diagram of the results of an in vitro drug release behavior test provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0030] In order to make the objects, features and advantages of the present application more obvious and understandable, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0031] In one embodiment of the present application, a nano-film silicon-based hydrogel drug-loaded contact lens comprises a contact lens body and a film containing drug molecules disposed on the surface of the contact lens body, wherein the thickness of the film is 0.5 to 10 microns, the pore size of the nanostructure monomer of the film is 50 nm to 1000 nm, and the contact lens body has an oxygen permeability coefficient of 100 to 150;

[0032] The contact lens is made of 0-90% of a contact lens substrate, 0.1-5% of a nanocarrier, 0-20% of a crosslinker and 0-8% of an initiator; wherein the nanocarrier is prepared from mesoporous silica and chitosan, the mesoporous silica has nanopores with different pore sizes, and the nanopores are loaded with hydrophilic or hydrophobic drug molecules.

[0033] It should be noted that the main component of the nanocarrier is chitosan, which has a small molecular size, a large surface area to volume ratio, good biocompatibility and the ability to form a film. It forms nanoparticle gel through the gelation process between ions. The nanofilm is mainly prepared by cross-linking the polyanionic crosslinker with the positively charged polycationic chitosan under the action of electrostatic adsorption.

[0034] Nanostructured films have the effect of sustained drug release, fast drug loading speed, can be used repeatedly, and can be used in combination with a variety of drug ingredients; they can relatively improve the hydrophilicity of the lens.

[0035] In the embodiments of the present application, with respect to the technical problem in the prior art that "the current drug-loaded silicone hydrogel contact lenses have a general drug loading amount, resulting in their efficacy failing to meet expectations", the present application provides a solution for loading drug molecules with nanocarriers having nanopores of different pore sizes, specifically: comprising a contact lens body and a film containing drug molecules disposed on the surface of the contact lens body, the film having a thickness of 0.5 to 10 microns, a nanostructure monomer pore size of 50nm-1000nm, and the contact lens body having an oxygen permeability coefficient of 100-150; the contact lens is made of a contact lens substrate accounting for 0-90%, a nanocarrier of 0.1-5%, a cross-linker of 0-20% and an initiator of 0-8%; wherein the nanocarrier is prepared from mesoporous silica and chitosan, the mesoporous silica having nanopores of different pore sizes, and the nanopores are loaded with hydrophilic or hydrophobic drug molecules. By using nanocarriers with different pore sizes to load drug molecules of different molecular weights, silicone hydrogel contact lenses have the functions of large-scale drug loading and sustained release, which prolongs the retention time of drugs in the eye. With high oxygen permeability, they can significantly improve drug retention rate, reduce adverse reactions, and allow continuous eye treatment.

[0036] Next, a nano-thin film silicon-based hydrogel drug-loaded contact lens in this exemplary embodiment will be further described.

[0037] In one embodiment of the present application, the drug molecule solution includes ophthalmic drug molecules and a drug solvent;

[0038] The ophthalmic drug molecules include one or more of ketotifen, levofloxacin, lomefloxacin, moxifloxacin, gentamicin, tetracycline hydrochloride or tobramycin, vitamin B12, vitamin B6, vitamin E, polymyxin sulfate, dexamethasone, hydroxypropyl methylcellulose and hyaluronic acid;

[0039] The drug solvent includes one or more of water, PBS buffer, polyethylene glycol, acetic acid solution, ethanol and physiological sodium chloride solution.

[0040] It should be noted that the nanocarriers carry ophthalmic drug molecules and evenly disperse the ophthalmic drug molecules in the contact lens. Mesoporous silica with different pore sizes increases the loading capacity of the nanocarriers, and the drug-loaded nanofilm is sandwiched between the homogeneous lens matrix. In the tear environment, the positively charged chitosan gradually diffuses the drug to the film surface due to its good bioadhesion and enhanced permeability, penetrating the silicon-based hydrogel to achieve sustained drug release.

[0041] In one embodiment of the present application, the contact lens substrate comprises 35-65% siloxane monomers, 35-65% hydrophilic monomers and 0.01-0.5% color dyes.

[0042] In one embodiment of the present application, the siloxane monomer includes one or more of bis-3-methacryloxypropylated tetramethyldisiloxane, methacryloxypropyl tris(trimethylsiloxy)silane, 3-methacryloxypropyl triethoxysilane, 3-methacryloxypropyl methyldiethoxysilane, and (3-methacryloxy-2-hydroxypropoxy)propyl bis(trimethylsiloxy)methyl.

[0043] It should be noted that since the solubility of oxygen in siloxane is much higher than in water, siloxane monomers can significantly increase the oxygen permeability coefficient of the lens, allowing silicone-based hydrogel contact lenses to achieve high oxygen permeability.

[0044] In one embodiment of the present application, the hydrophilic monomer includes one or more of hydroxyethyl methacrylate, N-vinyl pyrrolidone, methacrylic acid, methyl methacrylate and polyethylene glycol methacrylate.

[0045] It should be noted that hydrophilic monomers can form hydrogen bonds with water molecules to keep the lens surface moist, thereby reducing dryness and discomfort in the eyes. At the same time, hydrophilic monomers can also help improve the biocompatibility of lenses, reduce irritation and rejection reactions to eye tissues, and enhance the moisture retention and comfort of silicone-based hydrogel contact lenses.

[0046] In one embodiment of the present application, the color fuel includes one or more of benzidine yellow, carbon black, phthalocyanine blue, phthalocyanine green, iron oxide violet, iron oxide black, iron oxide red, iron oxide yellow and titanium dioxide.

[0047] It should be noted that the color dye adds color to the contact lenses, meeting consumers' demands for beauty and personalization.

[0048] In one embodiment of the present application, the crosslinking agent includes one or more of PVA, PVP, PEO, PAA, hyaluronic acid, polysiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, mercaptopropionic acid, citric acid and polyether polyurethane acrylate macromolecular crosslinking agents.

[0049] It should be noted that the crosslinking agent crosslinks the siloxane monomer and the hydrophilic monomer to form a gel material with a three-dimensional network structure, which makes the lens have excellent elasticity and flexibility.

[0050] In one embodiment of the present application, the initiator includes one of 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile) and phenylbisphosphine oxide.

[0051] It should be noted that the initiator is used to initiate a polymerization reaction between polymer compounds, thereby forming a desired gel material.

[0052] Reference Figure 1 , showing a method for preparing a nano-thin film silicon-based hydrogel drug-loaded contact lens provided in one embodiment of the present application;

[0053] The method comprises:

[0054] S110, uniformly mixing the drug molecules, the nanocarrier, the contact lens substrate, the cross-linking agent and the initiator to obtain a mixed solution;

[0055] S120, spraying the mixed solution on the surface of the contact lens body to form a thin film to obtain a target contact lens.

[0056] Next, a method for preparing a nano-thin film silicon-based hydrogel drug-loaded contact lens in this exemplary embodiment will be further described.

[0057] As described in step S110, the drug molecules, the nanocarriers, the contact lens substrate, the cross-linking agent and the initiator are uniformly mixed to obtain a mixed solution.

[0058] As an example, ophthalmic drug molecules are first dissolved in a drug solvent, such as water, PBS buffer, polyethylene glycol, acetic acid solution, ethanol or physiological sodium chloride solution to obtain a drug molecule solution. Weigh 5-15 mg of mesoporous silica, add 3-6 mL of drug molecule solution, add 150-250 μL of (3-aminopropyl) triethoxysilane, stir magnetically for 24 hours, centrifuge twice, dry the precipitate, and obtain a nanocarrier loaded with drug molecules. According to the proportion, 0-90% of the contact lens substrate (35-65% siloxane monomer, 35-65% hydrophilic monomer and 0.01-0.5% color dye), 0.1-5% of the nanocarrier, 0-20% of the crosslinker and 0-8% of the initiator are mixed evenly to obtain a mixed solution.

[0059] As described in step S120, the mixed solution is sprayed on the surface of the contact lens body to form a thin film to obtain a target contact lens.

[0060] As an example, the mixed solution obtained above is sprayed onto the surface of the contact lens body to form a thin film on the surface of the contact lens body with a thickness of 0.5 to 10 microns, thereby obtaining a nano-thin film silicone-based hydrogel drug-loaded contact lens.

[0061] Reference Figure 2 In one embodiment of the present application, it further includes:

[0062] S010, mixing a silica template, a polyether and pure water, adding a sodium hydroxide solution, and heating the mixture at 40-60° C. for 1-2 hours; wherein the silica template comprises one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium toluenesulfonate;

[0063] S020, mixing the mixed solution with tetraethoxysilane, and reacting at 50-70° C.;

[0064] S030, purifying the reaction product, and calcining at 500-600° C. for 5-7 hours to obtain mesoporous silica;

[0065] S040, mixing the chitosan solution, the mesoporous silica and sodium tripolyphosphate for 0.5 h, centrifuging and drying to obtain the nanocarrier; wherein the solvent of the chitosan solution is 2% acetic acid solution.

[0066] As an example, 40-180 mg of silica template and 4-18 mg of polyether are weighed and dissolved in 20-120 mL of pure water, and then 70-600 μL of NaOH solution is added, the mixture is heated to 40-60 ° C, and stirred for 1-2 hours; the temperature is raised to 50-70 ° C, and 250-1000 μL of tetraethoxysilane is added at the same time; the reaction product is purified, and then the sample is placed in a muffle furnace and calcined at 500-600 ° C for 5-7 hours to obtain mesoporous silica. The present application first uses a relatively low temperature of 40-60 ° C to stir and dissolve the relevant components. Subsequently, the first temperature is raised to 50-70 ° C for the synthesis reaction to construct a mesoporous structure with different pore sizes. The size of the pores is regulated by controlling the concentration of tetraethoxysilane.

[0067] Weigh 60-100 mg of chitosan, add it to 5-20 mL of 2% acetic acid solution, stir for half an hour to dissolve, and obtain a chitosan solution. Weigh 3-8 mg of mesoporous silica, add it to the chitosan solution and stir for half an hour; then weigh 5-15 mL of 0.5% sodium tripolyphosphate, add it to the above solution, and stir for half an hour. Finally, centrifuge and dry the precipitate to obtain the nanocarrier.

[0068] Example 1

[0069] Weigh 150 mg of hexadecyltrimethylammonium bromide and 15 mg of polyether, dissolve them in 120 mL of pure water, add 400 μL of NaOH solution, mix and heat to 50°C, and stir for 1 hour; raise the temperature to 60°C and add 500 μL of tetraethoxysilane; purify the reaction product, and then place the sample in a muffle furnace and calcine at 550°C for 6 hours to obtain mesoporous silica.

[0070] Weigh 80 mg of chitosan, add it to 10 mL of 2% acetic acid solution, stir for half an hour to dissolve, and obtain a chitosan solution. Weigh 5 mg of the above mesoporous silica, add it to the chitosan solution and stir for half an hour; then weigh 10 mL of 0.5% sodium tripolyphosphate, add it to the above solution, and stir for half an hour. Finally, centrifuge and dry the precipitate to obtain the nanocarrier.

[0071] Levofloxacin was dissolved in polyethylene glycol to obtain a drug molecule solution. 10 mg of mesoporous silica was weighed, added to 4 mL of the drug molecule solution, 200 μL of (3-aminopropyl) triethoxysilane was added dropwise, magnetic stirring was performed for 24 hours, centrifuged twice, and the precipitate was dried to obtain a nanocarrier loaded with drug molecules. According to weight, 80 parts of contact lens substrate (61.5% bis-3-methylpropyleneoxypropylated tetramethyldisiloxane, 38% N-vinylpyrrolidone and 0.5% benzidine yellow), 5 parts of nanocarrier, 10 parts of crosslinking agent and 5 parts of initiator were taken, and the above materials were mixed evenly to obtain a mixed solution. The mixed solution was sprayed onto the surface of the contact lens body to form a thin film on the surface of the contact lens body, and the film thickness was 2 microns.

[0072] Example 2

[0073] The preparation method of the nano-thin film silicon-based hydrogel drug-loaded contact lens of Example 2 is substantially the same as that of Example 1, except for the preparation method of the mesoporous silica.

[0074] Weigh 150 mg of hexadecyltrimethylammonium bromide and 15 mg of polyether, dissolve them in 120 mL of pure water, add 400 μL of NaOH solution, mix and heat to 60°C for reflux for 15 minutes; then add 500 μL of tetraethoxysilane dropwise and stir for 2 hours; centrifuge the sample, dry the precipitate, and then place the sample in a muffle furnace and calcine at 550°C for 6 hours to obtain mesoporous silica.

[0075] Oxygen permeability test:

[0076] Oxygen permeability is an important property of contact lenses. The oxygen permeability of Example 1 was tested multiple times using a coulometric oxygen permeator. The test results showed that the oxygen permeability of the corneal contact lenses of Example 1 was 100-150 barrer.

[0077] In vitro drug release behavior test:

[0078] In vitro drug release experiments were performed on Example 1, Example 2 and the nanocarrier in Example 1.

[0079] The experiment was carried out in PBS buffer solution at 35°C. 1 mL of the solution outside the dialysis bag was taken out at regular intervals and supplemented with 1 mL of fresh PBS buffer solution. The UV absorption of the solution at 292 nm was calculated by UV spectrophotometer, and the drug concentration and cumulative release were calculated by comparing with the standard curve. The experimental results are shown in Figure 2. Figure 3 shown.

[0080] from Figure 3 It can be seen that the loading rate of the nanocarrier is relatively fast, and the drug release reaches 63.4% in 24 hours and 81.5% in 48 hours. The contact lens of Example 2 releases 39.4% of the drug in 48 hours and 49.7% in 72 hours. The drug release of Example 1 is only 11.7% in 24 hours, 39.6% in 96 hours, and 50.6% after 10 days. It can be seen that the nano-thin film silicon-based hydrogel drug-loaded contact lens prepared in Example 1 can effectively prolong the release time of the drug.

[0081] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.

[0082] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.

[0083] The above is a detailed introduction to a nano-thin film silicon-based hydrogel drug-loaded contact lens and a preparation method thereof provided by the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for a person skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A nano-thin film silicon-based hydrogel drug-loaded contact lens, characterized in that: It comprises a contact lens body and a film containing drug molecules disposed on the surface of the contact lens body, wherein the thickness of the film is 0.5 to 10 microns, the pore size of the nanostructure monomer of the film is 50nm-1000nm, and the contact lens body has an oxygen permeability coefficient of 100-150; The contact lens is made of 0-90% of a contact lens substrate, 0.1-5% of a nanocarrier, 0-20% of a crosslinker and 0-8% of an initiator; wherein the nanocarrier is prepared from mesoporous silica and chitosan, the mesoporous silica has nanopores with different pore sizes, and the nanopores are loaded with hydrophilic or hydrophobic drug molecules.

2. The contact lens according to claim 1, characterized in that The drug molecule solution includes ophthalmic drug molecules and a drug solvent; The ophthalmic drug molecules include one or more of ketotifen, levofloxacin, lomefloxacin, moxifloxacin, gentamicin, tetracycline hydrochloride or tobramycin, vitamin B12, vitamin B6, vitamin E, polymyxin sulfate, dexamethasone, hydroxypropyl methylcellulose and hyaluronic acid; The drug solvent includes one or more of water, PBS buffer, polyethylene glycol, acetic acid solution, ethanol and physiological sodium chloride solution.

3. The contact lens according to claim 1, characterized in that The contact lens substrate comprises 35-65% of siloxane monomer, 35-65% of hydrophilic monomer and 0.01-0.5% of color dye.

4. The contact lens according to claim 3, characterized in that The siloxane monomer includes one or more of bis-3-methacryloxypropylated tetramethyldisiloxane, methacryloxypropyl tris(trimethylsiloxy)silane, 3-methacryloxypropyl triethoxysilane, 3-methacryloxypropyl methyldiethoxysilane, and (3-methacryloxy-2-hydroxypropoxy)propyl bis(trimethylsiloxy)methyl.

5. The contact lens according to claim 3, characterized in that The hydrophilic monomer includes one or more of hydroxyethyl methacrylate, N-vinyl pyrrolidone, methacrylic acid, methyl methacrylate and polyethylene glycol methacrylate.

6. The contact lens according to claim 3, characterized in that The color fuel includes one or more of benzidine yellow, carbon black, phthalocyanine blue, phthalocyanine green, iron oxide violet, iron oxide black, iron oxide red, iron oxide yellow and titanium dioxide.

7. The contact lens according to claim 1, characterized in that The crosslinking agent includes one or more of PVA, PVP, PEO, PAA, hyaluronic acid, polysiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, mercaptopropionic acid, citric acid and polyether polyurethane acrylate macromolecular crosslinking agents.

8. The contact lens according to claim 1, characterized in that The initiator includes one of 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile) and phenylbisphosphine oxide.

9. A method for preparing the nano-thin film silicon-based hydrogel drug-loaded contact lens as claimed in claim 1, characterized in that: Includes steps: uniformly mixing the drug molecules, the nanocarrier, the contact lens substrate, the crosslinking agent and the initiator to obtain a mixed solution; The mixed solution is sprayed on the surface of the contact lens body to form a thin film to obtain the target contact lens.

10. The preparation method according to claim 9, characterized in that: Also includes: Mixing a silica template, polyether and pure water, adding a sodium hydroxide solution, and heating the mixture at 40-60° C. for 1-2 hours; wherein the silica template comprises one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium toluenesulfonate; The mixed solution is mixed with tetraethoxysilane and reacted at 50-70° C.; Purifying the reaction product and calcining it at 500-600° C. for 5-7 hours to obtain mesoporous silica; The chitosan solution, the mesoporous silica and sodium tripolyphosphate are mixed and stirred for 0.5 h, and then centrifuged and dried to obtain the nanocarrier; wherein the solvent of the chitosan solution is 2% acetic acid solution.